Comparative study of six alternative solutions as fixatives for histological studies - Cauila, Jojo D. (The Philippine Journal of Veterinary Medicine, 2021)
This study was conducted to compare the efficiency of six alternative fixative solutions with formalin solution for histological studies. Skeletal muscle, lungs, jejunum, and liver were used for histological study collected from one non-descript dog, fixed with the six alternative solutions and formalin solution, then subjected to routine paraffin technique at 24 hours, 48 hours, and 72 hours post-fixation. Results revealed that the alternative fixing solutions were less effective compared to formalin fixation. Formalin solution was still the best solution for tissue fixation although alternative fixative solutions presented in the study can be used but only for a limited time period of 24 hours. Moreover, the use of Modified Weigner’s solution 2 composed of nitrite pickling salt, glycerin, water, sodium lauryl sulfate, and benzalkonium chloride showed that it was not a good fixative to use in histological studies.